A critical analysis of the environmental dossiers from the OECD sponsorship programme for the testing of manufactured nanomaterials. Issue 2 (14th December 2016) - Hansen, Steffen Foss; Hjorth, Rune; Skjolding, Lars Michael; Bowman, Diana M.; Maynard, Andrew; Baun, Anders
Abstract : In 2015, the OECD finally published the findings of its seven year testing programme for manufactured nanomaterials. Abstract : In 2015, the OECD finally published the findings of its seven year testing programme for manufactured nanomaterials. Here, we present the first in-depth analysis of the published OECD dossiers with regards to data on physical and chemical properties, environmental fate and ecotoxicology. Each individual study in the dossiers was reviewed with regard to, among other, which OECD Test Guidelines (TG) were used, and the reliability assigned to the study. We furthermore analyzed in detail the suspension methods used, how media quality was quantified and physical and chemical characterization performed prior, during and/or at the end of the study. We find that the information in the dossiers present an incomplete portfolio of nanomaterial ecotoxicological evaluations that are difficult to draw substantive conclusions from and that most of the studies were not designed to investigate the validity of the OECD test guidelines. We acknowledge the effort of the OECD WPMN and recommend that a follow-on program is established with well-defined goals, end-points and direct funding to qualified research laboratories to ensure valid, rigorous, reproducible and efficient research.